25.3k views
4 votes
Express the series using sigma notation. -8 + 4 - 2 + 1.

Express the series using sigma notation. -8 + 4 - 2 + 1.-example-1
User Linibou
by
5.5k points

1 Answer

6 votes

Answer:

Option a.
\sum_(k=0)^(k=3)(-2)^(3-k)
.

Explanation:

In this question the given series is -8 + 4 - 2 + 1...

which can be written as
-2^(3)+2^(2)-2^(1)+2^(0)

Or
-2^((3-0))+2^((3-1))-2^((3-2))+2^((3-3))

Here the expression are ranging from 0 to 3.

Now we can see that it's an exponential series

Now we write it in the form of sigma notation


=\sum_(k=0)^(k=3)(-2)^(3-k)

So the answer is Option a.
\sum_(k=0)^(k=3)(-2)^(3-k)




User Eliteparakeet
by
5.4k points